-4(m-2)=6m+5

Simple and best practice solution for -4(m-2)=6m+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(m-2)=6m+5 equation:


Simplifying
-4(m + -2) = 6m + 5

Reorder the terms:
-4(-2 + m) = 6m + 5
(-2 * -4 + m * -4) = 6m + 5
(8 + -4m) = 6m + 5

Reorder the terms:
8 + -4m = 5 + 6m

Solving
8 + -4m = 5 + 6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6m' to each side of the equation.
8 + -4m + -6m = 5 + 6m + -6m

Combine like terms: -4m + -6m = -10m
8 + -10m = 5 + 6m + -6m

Combine like terms: 6m + -6m = 0
8 + -10m = 5 + 0
8 + -10m = 5

Add '-8' to each side of the equation.
8 + -8 + -10m = 5 + -8

Combine like terms: 8 + -8 = 0
0 + -10m = 5 + -8
-10m = 5 + -8

Combine like terms: 5 + -8 = -3
-10m = -3

Divide each side by '-10'.
m = 0.3

Simplifying
m = 0.3

See similar equations:

| Ab+c=b | | -114+7x=-2x+147 | | (v/8)-9=-13 | | -1/3-21/3 | | 5t(3-6t)= | | (v/8 | | X^3-2x=100 | | 35x^2-34x+8=0 | | 34=-2-x^2 | | 2w(4+3w)= | | 3+11=-2(6x-7) | | y(-5/3)=1 | | -5(0)+2x=-10 | | 9=38(3x+32) | | 5x-3=40x+4 | | 9 = 38(3x+32) | | 4x^2-7=15 | | -5(7+3m)=-140 | | 2x=6+2x | | 3x-12=3x+-3x | | 5(3x+6)=-49+19 | | 3p(3-2m)= | | 4k(3+2d)= | | 1/3x-1/4(0)=2 | | 2x+25=6x+33 | | 5/6+3j=-1/2 | | 3n^3/6n | | 16G^2-16G+3=0 | | 6/7y=30 | | -4x-2+7x=3x-2 | | (w+4)(w+5)=12 | | 3=1/2(3x-6) |

Equations solver categories